Update on stomata development and action under abiotic stress - Matkowski, Hubert; Daszkowska-Golec, Agata (Frontiers in Plant Science, 2023)
Stomata, key gatekeepers of plant hydration, have long been known to play a pivotal role in mitigating the impacts of abiotic stressors. However, the complex molecular mechanisms underscoring this role remain unresolved fully and continue to be the subject of research. In the context of water-use efficiency (WUE), a key indicator of a plant's ability to conserve water, this aspect links intrinsically with stomatal behavior. Given the pivotal role of stomata in modulating water loss, it can be argued that the complex mechanisms governing stomatal development and function will significantly influence a plant's WUE under different abiotic stress conditions. Addressing these calls for a concerted effort to strengthen plant adaptability through advanced, targeted research. In this vein, recent studies have illuminated how specific stressors trigger alterations in gene expression, orchestrating changes in stomatal pattern, structure, and opening. This reveals a complex interplay between stress stimuli and regulatory sequences of essential genes implicated in stomatal development, such as MUTE, SPCH, and FAMA. This review synthesizes current discoveries on the molecular foundations of stomatal development and behavior in various stress conditions and their implications for WUE. It highlights the imperative for continued exploration, as understanding and leveraging these mechanisms guarantee enhanced plant resilience amid an ever-changing climatic landscape.